Assessment of symmetry and parental satisfaction after use of customized nasal conformers in unilateral cleft lip repair: a randomized controlled clinical trial - Mahmoud Akram Khodir; Saeeda Mahmoud Osman; Hala Ragaa Ragab; Mamdouh Ahmed AboulHassan; Mona Samy Oraby (Head & Face Medicine)
Abstract Objectives To evaluate the effectiveness of customized nasal conformers used after unilateral cleft lip repair on nasal symmetry and parental satisfaction. Materials and methods Fourteen medically free, non-syndromic children aged 10–24 weeks with unilateral cleft lip were divided into two groups. All patients underwent primary repair using the Fisher technique. Group I received customized nasal conformers fabricated using digital models, while Group II did not. Anthropometric measurements, including nostril height and width, columella deviation angle, and nasolabial angle were used to assess nasal symmetry between both groups. Parental satisfaction was evaluated using the Cleft Evaluation Profile (CEP). Results At six months postoperatively, Group I showed no significant difference between cleft and non-cleft sides across all parameters. In contrast, Group II exhibited significant asymmetry in nostril height and width, although no significant difference was observed in the nasolabial angle. CEP scores showed significantly higher satisfaction in fathers for lip, nose, and profile, and in mothers for nose and profile. No significant difference was noted in teeth appearance for either parent group. Intra-examiner reliability was reliable across all parameters. Conclusions The use of customized postsurgical nasal conformers in unilateral cleft lip repair was associated with improved symmetry between cleft and non-cleft sides and appeared to reduce relapse, which may have contributed to increased parental satisfaction with the treatment. Trial registration Was retrospectively registered at Clinicaltrials.gov on 23/10/2024 (NCT06637488).